River Basin Management 2016
DOI: 10.5772/63713
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Floodplain Soils in the European North‐East of Russia

Abstract: River floodplains are unique nature landscapes. In contrast to zonal communities on watersheds, soil biota of river floodplains is studied in less degree. The research was conducted in the floodplain forests in the European NorthEast of Russia and showed high diversity of soil biota in alluvial forest soils. Floodplain forest soils are inhabited by 70 species of micromycetes, 53 genera of Nematoda, 60 species of Collembola, and 110 species of large invertebrates. Alluvial meadow soils with stable moisture and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…A brief summary of the topics and regions discussed in the presentations could be traced in the text below. In accordance to the studied regions, starting from Europe in eastern direction, the contributions can be ordered in the following way: from the European Russian Arctic at White and Barents Seas (Kolesnikova 2017;Kolesnikova et al 2017;Markovskaya et al 2017;Sergienko et al 2017), Northern Sea and Baltic Sea region (Andreev et al 2017) to the Mediterranean European coasts (Asenov 2017;Domina et al 2017;Laguna et al 2017), then through the Black Sea coastal region (Abramova et al 2017;Agafonova 2017;Bancheva 2017;Bancheva & Delcheva 2017;Boev 2017;Broshtilova et al 2017;Bryantseva 2017;Descy et al 2017;Dimitrov & Vutov 2017;Doycheva et al 2017a, b;Filipova-Marinova 2017;Gärtner et al 2017;Kozhuharova 2017;Maximilian et al 2017;Michev et al 2017;Nikolova et al 2017;Pavlova et al 2017;Petrova & Vladimirov 2017;Petrova et al 2017;Sadogurska 2017;Stoyneva-Gärtner et al 2017;Strat & Holobiuc 2017;Strat et al 2017;Tashev et al 2017a, b;Vinogradova & Bryantseva 2017;Vitkova et al 2017;Yankova-Tsvetkova 2017;Zhelev & Aneva 2017), Caspian Sea coast (Dimeeva et al 2017), Aral Sea (Bekniyaz et al 2017, Persian Gulf and Gulf of Oman of the Indian Ocean (Alhaj 2017) to...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A brief summary of the topics and regions discussed in the presentations could be traced in the text below. In accordance to the studied regions, starting from Europe in eastern direction, the contributions can be ordered in the following way: from the European Russian Arctic at White and Barents Seas (Kolesnikova 2017;Kolesnikova et al 2017;Markovskaya et al 2017;Sergienko et al 2017), Northern Sea and Baltic Sea region (Andreev et al 2017) to the Mediterranean European coasts (Asenov 2017;Domina et al 2017;Laguna et al 2017), then through the Black Sea coastal region (Abramova et al 2017;Agafonova 2017;Bancheva 2017;Bancheva & Delcheva 2017;Boev 2017;Broshtilova et al 2017;Bryantseva 2017;Descy et al 2017;Dimitrov & Vutov 2017;Doycheva et al 2017a, b;Filipova-Marinova 2017;Gärtner et al 2017;Kozhuharova 2017;Maximilian et al 2017;Michev et al 2017;Nikolova et al 2017;Pavlova et al 2017;Petrova & Vladimirov 2017;Petrova et al 2017;Sadogurska 2017;Stoyneva-Gärtner et al 2017;Strat & Holobiuc 2017;Strat et al 2017;Tashev et al 2017a, b;Vinogradova & Bryantseva 2017;Vitkova et al 2017;Yankova-Tsvetkova 2017;Zhelev & Aneva 2017), Caspian Sea coast (Dimeeva et al 2017), Aral Sea (Bekniyaz et al 2017, Persian Gulf and Gulf of Oman of the Indian Ocean (Alhaj 2017) to...…”
Section: Resultsmentioning
confidence: 99%
“…The biodiversity of lichens in coastal regions was reflected in the contributions of Andreev et al (2017) and Markovskaya et al (2017) Fauna and zoocoenoses of coastal areas were topics in the contributions by Boev (2017), Kolesnikova (2017), Kolesnikova et al (2017), ), Strat et al (2017. From taxonomic point of view these studies concerned both invertebrates (Kolesnikova 2017;Kolesnikova et al 2017;) and different vertebrates (Boev 2017;Strat et al 2017). The conservation of species and habitats of community importance, including flagship species was presented in particular by Strat et al (2017).…”
Section: Resultsmentioning
confidence: 99%
“…A brief summary of the topics and regions discussed in the presentations could be traced in the text below. In accordance to the studied regions, starting from Europe in eastern direction, the contributions can be ordered in the following way: from the European Russian Arctic at White and Barents Seas (Kolesnikova 2017;Kolesnikova et al 2017;Markovskaya et al 2017;Sergienko et al 2017), Northern Sea and Baltic Sea region (Andreev et al 2017) to the Mediterranean European coasts (Asenov 2017;Domina et al 2017;Laguna et al 2017), then through the Black Sea coastal region (Abramova et al 2017;Agafonova 2017;Bancheva 2017;Bancheva & Delcheva 2017;Boev 2017;Broshtilova et al 2017;Bryantseva 2017;Descy et al 2017;Dimitrov & Vutov 2017;Doycheva et al 2017a, b;Filipova-Marinova 2017;Gärtner et al 2017;Kozhuharova 2017;Maximilian et al 2017;Michev et al 2017;Nikolova et al 2017;Pavlova et al 2017;Petrova & Vladimirov 2017;Petrova et al 2017;Sadogurska 2017;Stoyneva-Gärtner et al 2017;Strat & Holobiuc 2017;Strat et al 2017;Tashev et al 2017a, b;Vinogradova & Bryantseva 2017;Vitkova et al 2017;Yankova-Tsvetkova 2017;Zhelev & Aneva 2017), Caspian Sea coast (Dimeeva et al 2017), Aral Sea (Bekniyaz et al 2017, Persian Gulf and Gulf of Oman of the Indian Ocean (Alhaj 2017) to...…”
Section: Resultsmentioning
confidence: 99%
“…The results of our research showed that the wetland habitats of the Danube, Begej and Tisa Rivers could provide suitable conditions for rove beetle communities with high species richness. Also, according to Kolesnikova et al (2016), rove beetles are characterized by high species diversity in wetlands and alluvial forest. According to Derunkov (2009), wetland ecosystems in general, especially oodplain forests are key habitats for many rare species, including postglacial relicts.…”
Section: Discussionmentioning
confidence: 99%